Baseball, Modernity, and Science Discourse in British Popular Culture, 1871–1883. (December 2022) - Beaver, Daniel C.
Abstract: Baseball in the United Kingdom has long been considered a contradiction in terms, especially during the nineteenth century, with both the 1874 National Association Tour and the 1888 Spalding Tour viewed as financial and cultural failures in a sophisticated consumer society already dominated by cricket. This article takes a fresh look at evidence from the 1870s and 1880s in order to challenge this perspective. It presents the 1874 Tour as a transnational success, articulating shared Anglo-American assumptions about modernity, science, and social progress. This discourse informed a broad process of technology transfer involving new sources of industrial power as well as the corporal techniques of modern sport. The article also places the tour in the context of a unique historical phenomenon: the transatlantic diffusion of an early modern English game to the United Kingdom as the New York Game, a modern American sport. Previous accounts of the tour focused on a few selected reports, confirming American views of its financial failings and British disinterest in its exhibitions. When considered in light of hundreds of British accounts from the 1870s, including unexamined evidence of the first British baseball clubs less than two years after the tour, this perspective becomes unsustainable.